Biochemical markers of safety of nano-particles of metals on the model of isolated subcultural fractions of eukaryotes - M. Y. Roman’ko (Regulatory Mechanisms in Biosystems, 2017)
Unique sizes and a high level of bioavailability allow nanoparticles of metals (NPMe) to come into direct contact with biological systems, with infectious agents, toxins, as well as with different chemical compounds and separate cell structures (proteins, lipids, nucleic acids). Other biological effects, including less toxicity than in microscopic substances, require attention to be paid to the study of the potential risk of using nanoparticles of each type in a particular way, therefore scientific support is absolutely necessary in this direction. It is believed that the cytotoxicity of nanomaterials is due to genomic and mutagenic effects, but the mechanical forces of interaction of NPMе with cells, obviously, will change not only cytological but also their metabolic reactions. Therefore, the purpose of this research was to determine the biochemical markers of safety (potential toxicity) of NPMe (Au, Ag, Cu, Fe, Co, GFCo, Zn, MnO2) on the model of isolated membrane and cytosolic fractions of eukaryotic test cells of CHO-K1 and U937 lines. Under conditions of preincubation of experimental samples of NPMe at a final concentration of 1 μg/cm3 by the metal with preparations of subcellular fractions of CHO-K1 and U937 (in the final amount of protein 150–200 μg/cm3) for 3 minutes at 37 ± 1 ºС, there was determined the magnitude of membrane ATP-ase and cytosolic LDH-ase activity compared to intact cells ("control"). According to the results of the research, colloidal dispersions of NPAg average size ~30 nm, NPFe ~100 nm, NPCu ~70 nm, and NPMnO2 ~50 nm are safe and biocompatible by their membranotropic effect on subcellular fractions of eukaryotic test cells, as evidenced by an increase in the level of membrane ATPase and cytosolic LDHase of test-cells CHO-K1, and the experimental samples NPCo, NPGFCo and NPZn average size of ~100 nm are membrane-toxic, that is, dangerous. By the nature of the changes in the enzymatic activity of the test cells U937, the discrete dimensions of the membranotropic action of NPAu have been demonstrated: nanoparticles of size ~10 nm caused the inhibition of the membrane Na+,K+-ATPase, and the size of ~30 nm and ~45 nm – its induction; nanoparticles of size ~10, ~20 and ~30 nm induced cytosolic LDHase and the size of ~45 nm – its inhibition relative to the control level of enzymes, so NPAu ~10 and ~45 nm can be considered membrane toxic, and size ~30 nm – safe and biocompatible for eukaryotic cells. Based on the hypothesis about the involvement of metabolism-dependent mechanisms of contact interaction of colloidal dispersions of experimental samples of NPMe with cells through membranotropic properties, the study of their potential danger or biocompatibility in further research can be carried out by determining the intensity of oxidation of the main structural components of biomembranes of cells – lipids and proteins and indicators of their AO-regulation.